Electrochemical device

CN116420209BActive Publication Date: 2026-10-27PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202180072151.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-10-27
Filing Date
2021-10-26
Publication Date
2026-10-27
Estimated Expiration
2041-10-26

AI Technical Summary

Benefits of technology

[0009]根据本发明,能够提供兼顾高容量和高输出特性的电化学器件。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116420209B_ABST
    Figure CN116420209B_ABST
Patent Text Reader

Abstract

The electrochemical device of the present application has an electrode body and an electrolyte containing a lithium salt, the electrode body has a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, the negative electrode has a negative electrode current collector and a negative electrode mixture layer supported on the negative electrode current collector, the negative electrode mixture layer contains a negative electrode active material that reversibly dopes lithium ions, the negative electrode current collector substantially has no through holes, the specific surface area of the negative electrode mixture layer is 30 m 2 / g or more and 60 m 2 / g or less, and in a discharged state, the potential of the negative electrode is set to 0.2 V or less with reference to a Li counter electrode, thereby enabling high capacity and high output to be balanced at a high level.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to electrochemical devices. Background Technology

[0002] In recent years, electrochemical devices combining the energy storage principles of lithium-ion batteries and electric double-layer capacitors have attracted much attention. Such devices typically use a polarized electrode as the positive electrode and a non-polarized electrode as the negative electrode. The goal is to achieve both the high energy density of lithium-ion batteries and the high output characteristics of electric double-layer capacitors.

[0003] Patent document 1 discloses a negative electrode film for a lithium-ion capacitor, characterized in that it is formed by coating a coating composition for forming an electrode film containing non-graphitizable carbon, a conductive additive, and a binder in an aqueous medium containing a dispersant onto a metal foil, and then heating and drying it to form a film. The conductive additive includes at least one of Ketjen black, acetylene black, and graphite, and the particle size distribution of the constituent particles in the negative electrode film is: D 10 Particle size greater than 0.5μm, D 50 Particle size range of 1–4 μm, D 90 The particle size is below 8 μm, and the specific surface area of ​​the negative electrode film is 1.5–25 m². 2 The range is / g, and the surface roughness of the negative electrode film is in the range of 0.1 to 0.3 μm.

[0004] Existing technical documents

[0005] Patent documents

[0006] Patent Document 1: Japanese Patent Application Publication No. 2010-98020 Summary of the Invention

[0007] However, in electrochemical devices like those described above, further improvements are needed to achieve a higher level of balance between high capacity and high output characteristics.

[0008] An electrochemical device according to one aspect of the present invention includes an electrode body and an electrolyte comprising a lithium salt. The electrode body includes a positive electrode, a negative electrode, and a spacer between the positive electrode and the negative electrode. The negative electrode includes a negative electrode current collector and a negative electrode additive layer supported on the negative electrode current collector. The negative electrode additive layer contains a negative electrode active material reversibly doped with lithium ions, and the negative electrode current collector substantially does not have through-pores. The specific surface area of ​​the negative electrode additive layer is 30 m² / g. 2 / g or more and 60m 2 / g or less, in the discharge state, the potential of the above negative electrode is 0.2V or less with reference to the Li counter electrode.

[0009] According to the present invention, an electrochemical device that combines high capacity and high output characteristics can be provided. Attached Figure Description

[0010] Figure 1 This is a longitudinal cross-sectional view of an electrochemical device according to one embodiment of the present invention. Detailed Implementation

[0011] The electrochemical device according to embodiments of the present invention includes an electrode body and an electrolyte containing a lithium salt. The electrode body includes a positive electrode, a negative electrode, and a spacer between the positive and negative electrodes. For example, the electrode body can be configured as a cylindrical wound body by winding strip-shaped positive and negative electrodes with the spacer in between. Alternatively, the electrode body can be configured as a laminate by stacking plate-shaped positive and negative electrodes with the spacer in between.

[0012] The negative electrode comprises a negative current collector and a negative electrode additive layer supported on the negative current collector. The negative electrode additive layer contains a negative electrode active material reversibly doped with lithium ions. Capacity is exhibited in the negative electrode through a Faraday reaction that reversibly absorbs and releases lithium ions. Lithium ion doping into the negative electrode active material refers to a concept that includes at least the absorption and storage of lithium ions into the negative electrode active material, and may also include lithium ion adsorption into the negative electrode active material, chemical interactions between the negative electrode active material and lithium ions, etc.

[0013] The potential of the negative electrode increases with discharge. In the case of a typical lithium-ion secondary battery, the potential of the negative electrode in a fully discharged state is, for example, 1V, exceeding 0.2V relative to the Li counter electrode. In contrast, the electrochemical device of this embodiment has a negative electrode potential of less than 0.2V relative to the Li counter electrode in the discharged state. This means that there is sufficient lithium doping in the negative electrode even in the discharged state. Such a negative electrode is obtained by pre-doping lithium ions into the negative electrode before charging the manufactured device. By using a pre-doped negative electrode, high capacity can be achieved.

[0014] Here, the discharge state refers to the state at 25°C with a discharge rate of 2 mA / cm² per unit positive electrode area. 2 An electrochemical device charged at a constant current density to a voltage corresponding to more than 95% of its state of charge (SOC) (e.g., 3.8V) at 25°C with an A / cm² current density of 2 mA / cm². 2 The device is discharged at a constant current density until the voltage reaches a state corresponding to more than 95% of the depth of discharge (DOD) (e.g., 2.2V). The potential of the negative electrode is determined by disassembling the device after charging and discharging under the above conditions, using the removed negative electrode as the working electrode, using the Li metal foil as the counter electrode, assembling a half-cell, and measuring the potential of the negative electrode relative to the Li metal foil.

[0015] Electrochemical devices with pre-doped lithium-ion negative electrodes differ from typical lithium-ion secondary batteries in that they are characterized by rapid charging and discharging, and the ability to achieve high output. To achieve rapid charging and discharging and high output, foils with through-holes for good electrolyte circulation are typically used as the negative electrode current collector in electrochemical devices. However, the presence of through-holes increases the current collector's resistance, sometimes preventing the achievement of high output. There are limits to improving output characteristics when using foils with through-holes.

[0016] Furthermore, when using foils with through holes, the foil's strength decreases, and it sometimes breaks due to tensile stress. Especially when using a wound body formed by winding the positive and negative electrodes with spacers as the electrode body, the wound body expands (and contracts) during charging and discharging, applying tensile (and compressive) stress to the current collector. As a result, current collectors with through holes are prone to breakage. To suppress breakage of current collectors with through holes and reduce resistance to achieve high output, the thickness of the current collector can be increased. However, if the current collector thickness is increased, the thickness of the negative electrode flux layer correspondingly becomes thinner, or the area of ​​the negative electrode decreases without changing the thickness of the negative electrode flux layer. As a result, it is difficult to obtain high capacity.

[0017] In the electrochemical device of this embodiment, a negative current collector that is substantially without through-holes is used. This suppresses the increase in resistance, ensuring the strength of the negative current collector while achieving high output, and suppressing breakage of the winding during charging and discharging. Furthermore, the negative current collector can be made thinner while ensuring its strength, thus easily increasing the thickness of the negative electrode binder layer or the area of ​​the negative electrode. Through the synergistic effect with the use of a pre-doped negative electrode, high capacity can be easily achieved. It should be noted that, regarding the negative current collector, "substantially without through-holes" means that the aperture ratio of the negative current collector is, for example, 1% or less. The aperture ratio of the negative current collector refers to the ratio of the area of ​​the opening portion existing in the main surface of the negative current collector to the area of ​​the main surface.

[0018] Furthermore, the electrochemical device of this embodiment has a specific surface area of ​​30 m² for the negative electrode binder layer. 2 / g or higher. This allows for higher output. The specific surface area of ​​the negative electrode mixture layer is more preferably 40m². 2 / g or more. On the other hand, from the viewpoint of suppressing the increase of side reactions and maintaining high cycling characteristics, the specific surface area of ​​the negative electrode mixture layer is 60m². 2 / g or less, preferably 50m 2 / g or less.

[0019] It should be noted that the specific surface area of ​​the negative electrode additive layer can be adjusted to the desired value by changing the materials, properties (e.g., particle size, specific surface area), and proportions of the negative electrode active material, binders, and conductive additives that may be included in the negative electrode active material. The specific surface area of ​​the conductive additive can be 800 m². 2 / g or more. This facilitates the formation of a negative electrode additive layer with the desired specific surface area. A more preferred specific surface area for the conductive additive is 800 m². 2 / g or more and 1500m 2 / g or less.

[0020] The specific surface area of ​​the negative electrode binder layer was determined using a BET specific surface area measured according to JIS Z8830 (e.g., the TriStar II3020 manufactured by Shimadzu Corporation). Specifically, the electrochemical device was disassembled, and the negative electrode was removed. This negative electrode was used as the working electrode, and a Li metal foil was used as the counter electrode to assemble a half-cell, allowing the Li in the negative electrode to be dedoped until the negative electrode potential reached 1.5V. Next, the Li-dedoped negative electrode was cleaned with dimethyl carbonate (DMC) and dried. Then, the negative electrode binder layer was peeled off from the negative electrode current collector, and approximately 0.5g of the negative electrode binder layer sample was collected.

[0021] Next, the collected sample was heated at 150°C for 12 hours under reduced pressure below 95 kPa. Then, nitrogen gas was adsorbed onto the sample of known mass, and adsorption isotherms were obtained within a relative pressure range of 0 to 1. The surface area of ​​the sample was then calculated based on the monolayer adsorption amount of the gas obtained from the adsorption isotherms. Here, the specific surface area was determined using the BET one-point method (relative pressure 0.3) according to the following BET formula.

[0022] P / V(P0-P)=(1 / VmC)+{(C-1) / VmC}(P / P0)··(1)

[0023] S=kVm··(2)

[0024] P0: Saturated vapor pressure

[0025] P: Adsorption equilibrium pressure

[0026] V: Adsorption amount under adsorption equilibrium pressure P

[0027] Vm: Monolayer adsorption capacity

[0028] C: Parameters related to adsorption heat, etc.

[0029] S: Specific surface area

[0030] k: Nitrogen single molecule area is 0.162 nm 2

[0031] When a conductive additive is included in the negative electrode mixture layer, the content of the conductive additive in the negative electrode mixture layer is preferably 3% by mass or more and 15% by mass or less, more preferably 5% by mass or more and 10% by mass or less. If the content of the conductive additive is 3% by mass or more, the resistance of the negative electrode mixture layer decreases and the current collection performance improves. As a result, higher output can be achieved. On the other hand, if the content of the conductive additive is too large, the proportion of the negative electrode active material in the negative electrode mixture layer decreases, and sometimes high capacity cannot be obtained. In addition, with the increase of the specific surface area of ​​the negative electrode mixture layer, side reactions sometimes increase and cycle characteristics decrease. From the viewpoint of maintaining high capacity and high cycle characteristics, the content of the conductive additive is preferably 15% by mass or less or 10% by mass or less.

[0032] The content of the conductive additive was determined by the following method based on the conductive additive separated from the negative electrode binder layer. The electrochemical device was disassembled to remove the negative electrode, and a portion of the negative electrode binder layer was peeled off from the negative electrode, which had been dedoped with Li using the method described above. After washing the negative electrode binder layer with water to remove binders, etc., the conductive additive was separated by centrifugation. The content of the conductive additive is the ratio of the mass of the separated conductive additive to the mass of the negative electrode binder layer before washing.

[0033] The specific surface area of ​​the conductive additive is determined by the BET method, similar to the determination of the specific surface area of ​​the negative electrode layer for the conductive additive separated by the above method.

[0034] The negative electrode active material preferably contains non-graphitized carbon. Non-graphitized carbon is also known as hard carbon. By using hard carbon, high cycle characteristics can be obtained even under repeated fast charging and discharging conditions. In this case, the negative electrode binder layer preferably contains carbon black as a conductive additive. Carbon black has a large specific surface area, which easily increases the specific surface area of ​​the negative electrode binder layer. In addition, carbon black is easily coated with hard carbon, thus easily improving the adhesion between the negative electrode active materials.

[0035] The thickness of the negative electrode current collector can be 15 μm or less. As described above, in the electrochemical device of this embodiment, since the aperture ratio of the negative electrode current collector is small, the strength can be maintained even if the thickness of the negative electrode current collector is reduced. By reducing the thickness of the negative electrode current collector and increasing the thickness of the negative electrode binder layer, high capacity can be achieved. The thickness of the negative electrode current collector is preferably 10 μm or less, more preferably 8 μm or less. On the other hand, reducing the thickness of the negative electrode current collector sometimes leads to increased resistance, making it impossible to obtain high output. In order to maintain high output, the thickness of the negative electrode current collector is preferably 3 μm or more, more preferably 4 μm or more. The upper and lower limits of the above thickness can be combined arbitrarily.

[0036] The thickness of the negative electrode flux layer can be, for example, 25 μm or more, or 30 μm or more, or 32 μm or more. It should be noted that, in the above context, when the negative electrode flux layer is formed on both sides of the negative electrode current collector, the thickness of the negative electrode flux layer refers to the thickness on one side only.

[0037] The positive electrode comprises a positive current collector and a positive electrode binder layer supported on the current collector. The positive electrode binder layer contains a positive electrode active material reversibly doped with anions. If anions are adsorbed onto the positive electrode active material, an electrical double layer is formed, exhibiting capacity. The positive electrode can be a polarizable electrode, or an electrode with properties of a polarizable electrode in which the Faraday reaction also contributes to capacity.

[0038] The positive electrode active material can be a carbon material or a conductive polymer. Anion doping of the positive electrode active material refers to at least the adsorption of anions into the positive electrode active material, and may also include the absorption and storage of anions based on the positive electrode active material, and the chemical interaction between the positive electrode active material and anions.

[0039] Predoping of the negative electrode with lithium ions can be performed by contacting the negative electrode with an electrolyte that is conductive to lithium ions before assembling the device. For example, metallic lithium can be used as the lithium ion source for predoping. For instance, a working electrode (e.g., a stainless steel (SUS) plate) with a negative electrode and a lithium ion source mounted thereon is placed in an electrolytic cell filled with an electrolyte that is conductive to lithium ions, with a spacer between the negative and working electrodes. The working electrode is used as the positive electrode, and a voltage is applied between the positive and negative electrodes, thereby enabling predoping. The voltage can be applied, for example, under a specified constant current flowing between the positive and negative electrodes. The voltage application time is, for example, 1 to 75 hours.

[0040] Lithium metal, used as a lithium-ion source, can be pre-attached to the surface of the negative electrode additive layer. The negative electrode with lithium metal attached is then placed into the electrolytic cell, and a voltage is applied between the negative electrode and the working electrode to perform pre-doping.

[0041] The adhesion of metallic lithium to the surface of the negative electrode binder layer can be achieved through methods such as vapor phase deposition and transfer. Examples of vapor phase deposition methods include chemical vapor deposition, physical vapor deposition, and sputtering. For instance, metallic lithium can be formed into a film on the surface of the negative electrode binder layer using a vacuum vapor deposition apparatus. The pressure within the apparatus chamber during vapor deposition is set, for example, to 10⁻² to 10⁻⁶. -5 Pa is sufficient, the temperature of the lithium evaporation source is 400-600℃, and the temperature of the negative electrode binder layer is -20-80℃.

[0042] By exposing the negative electrode having a negative electrode binder layer with attached lithium metal to a carbon dioxide atmosphere, a lithium carbonate-containing layer (first layer) can be formed on the surface of the negative electrode binder layer. As described later, this lithium carbonate-containing layer can suppress the degradation of the negative electrode and suppress the rise of the low-temperature DC resistance (DCR) of the electrochemical device. The carbon dioxide atmosphere is preferably a dry atmosphere free of moisture, for example, with a dew point of -40°C or below or -50°C. The carbon dioxide atmosphere may contain gases other than carbon dioxide, and the mole fraction of carbon dioxide is preferably 80% or more, more preferably 95% or more. The carbon dioxide atmosphere preferably does not contain oxidizing gases, and the mole fraction of oxygen is preferably 0.1% or less. The partial pressure of carbon dioxide in the carbon dioxide atmosphere is, for example, greater than 0.5 atmospheres (5.05 × 10⁻⁶). 4 Pa) is highly efficient, and can also be 1 atmosphere (1.01 × 10⁻⁶). 5 (pa) and above.

[0043] By contacting the negative electrode with an electrolyte that is conductive to lithium ions, lithium ions can be pre-doped, and a layer containing a solid electrolyte (second layer) can be formed on the surface of the negative electrode. The second layer serves as a solid electrolyte interfacial film (i.e., an SEI film). When a first layer is formed on the surface of the negative electrode mixture layer, the second layer can be formed in a manner that covers at least a portion of the first layer. The first layer containing lithium carbonate has the function of promoting the formation of a good SEI film and maintaining the SEI film in a good state during repeated charge and discharge.

[0044] Hereinafter, the positive and negative electrodes will sometimes be collectively referred to as electrodes. Additionally, the positive and negative current collectors will sometimes be collectively referred to as current collectors (or electrode current collectors). Furthermore, the positive and negative flux layers will sometimes be collectively referred to as flux layers (or electrode flux layers). Finally, the positive and negative active materials will sometimes be collectively referred to as active materials (or electrode active materials).

[0045] Figure 1The configuration of an electrochemical device 200 according to one embodiment of the present invention is schematically shown. The electrochemical device 200 includes: an electrode body 100, a non-aqueous electrolyte (not shown), a bottomed metal battery casing 210 housing the electrode body 100 and the non-aqueous electrolyte, and a sealing plate 220 sealing the opening of the battery casing 210. A gasket 221 is disposed at the periphery of the sealing plate 220, and the interior of the battery casing 210 is sealed by riveting the open end of the battery casing 210 to the gasket 221. A positive electrode current collector 13 having a through hole 13h in the center is welded to the exposed portion 11x of the positive electrode current collector. The other end of a connector lead 15 connected to the positive electrode current collector 13 is connected to the inner surface of the sealing plate 220. Therefore, the sealing plate 220 functions as an external positive terminal. On the other hand, a negative electrode current collector 23 is welded to the exposed portion 21x of the negative electrode current collector. The negative electrode current collector 23 is directly welded to a welding member provided on the inner bottom surface of the battery casing 210. Therefore, the battery casing 210 functions as an external negative electrode.

[0046] The constituent elements of the electrochemical device according to embodiments of the present invention will be described in more detail below.

[0047] (negative electrode)

[0048] The negative electrode comprises a negative electrode current collector and a negative electrode additive layer supported on the negative electrode current collector. The negative electrode additive layer contains a negative electrode active material reversibly doped with lithium ions, and the negative electrode active material contains non-graphitizable carbon (i.e., hard carbon). The thickness of the negative electrode additive layer on each single side of the negative electrode current collector is, for example, 10–300 μm. The thickness of the negative electrode additive layer on each single side of the negative electrode current collector can be 25 μm or more.

[0049] The negative current collector uses a sheet-like metal material that does not have through holes. Examples of sheet-like metal materials include metal foil. Suitable metal materials include copper, copper alloys, nickel, and stainless steel. The aperture ratio of the negative current collector can be less than 1%.

[0050] The negative current collector plate is a roughly disc-shaped metal plate. The material of the negative current collector plate can be, for example, copper, copper alloy, nickel, or stainless steel. The material of the negative current collector plate can be the same as that of the negative current collector itself.

[0051] The interplanar spacing (i.e., the interplanar spacing between carbon layers) d002 of the (002) plane of non-graphitizable carbon, as determined by X-ray diffraction, can be... The theoretical capacity of the non-graphitized carbon is preferably 150 mAh / g or more. By using non-graphitized carbon, it is easy to obtain a negative electrode with low low-temperature DCR and small expansion and contraction during charging and discharging. The non-graphitized carbon preferably accounts for 50% or more by mass of the negative electrode active material, more preferably 80% or more by mass, and even more preferably 95% or more by mass. In addition, the non-graphitized carbon preferably accounts for 40% or more by mass of the negative electrode binder layer, more preferably 70% or more by mass, and even more preferably 90% or more by mass.

[0052] As a negative electrode active material, materials other than non-graphitized carbon can be used in combination. Examples of materials other than non-graphitized carbon that can be used as a negative electrode active material include easily graphitized carbon (soft carbon), graphite (natural graphite, artificial graphite, etc.), lithium titanium oxide (spinel-type lithium titanium oxide, etc.), silicon oxide, silicon alloy, tin oxide, tin alloy, etc.

[0053] From the viewpoint that the negative electrode active material has high filling capacity and can easily suppress side reactions with the electrolyte, the average particle size of the negative electrode active material (especially the non-graphitized carbon) is preferably 1 μm to 20 μm, and more preferably 2 μm to 15 μm.

[0054] It should be noted that, in this specification, the average particle size refers to the median particle size (D0) of the volume reference in the particle size distribution obtained by laser diffraction particle size distribution measurement. 50 ).

[0055] The negative electrode binder layer contains a negative electrode active material as a necessary component, and optional components include conductive additives, binders, etc. Examples of conductive additives include carbon black and carbon fiber. Carbon black is preferred as a conductive additive. Examples of binders include fluororesins, acrylic resins, rubber materials, and cellulose derivatives.

[0056] The negative electrode binder layer is formed, for example, by mixing negative electrode active material, conductive agent and binder with a dispersion medium to prepare a negative electrode binder slurry, and then coating the negative electrode binder slurry onto the negative electrode current collector and drying it.

[0057] Lithium ions can be pre-doped into the negative electrode flux layer. This lowers the potential of the negative electrode, thus increasing the potential difference (i.e., voltage) between the positive and negative electrodes, and improving the energy density of the electrochemical device. The amount of pre-doped lithium can be set to approximately 50% to 95% of the maximum amount that the negative electrode flux layer can absorb and store.

[0058] The capacitance per unit mass of the negative electrode active material should be, for example, 1000 F / g or higher. However, from the viewpoint of improving the capacity density of the electrochemical device, the capacitance per unit mass of the negative electrode active material should be, for example, 30000 F / g or lower. The capacitance per unit mass of the negative electrode active material is typically greater than that of the positive electrode active material, for example, 20 to 800 times greater. It should be noted that the capacitance per unit mass of the negative electrode active material can be determined using the following method.

[0059] First, an evaluation negative electrode is prepared, cut to a size of 31mm × 41mm. As the counter electrode, a 100μm thick lithium metal foil, cut to a size of 40mm × 50mm, is prepared. The negative electrode mixture layer and the lithium metal foil are placed opposite each other, separated by a 25μm thick cellulose paper (e.g., product number TF4425) manufactured by Nippon High Paper Industry Co., Ltd., to form the electrode body. The electrode body is then impregnated in the electrolyte of Example 1 described later to assemble the battery.

[0060] The battery was charged at a constant current (CC) of 0.5mA until the battery voltage reached 0.01V, then charged at a constant voltage (CV) for 1 hour, and finally discharged at 0.5mA until the battery voltage reached 1.5V. The capacitance per unit mass of the negative electrode active material was calculated based on the discharge time from the negative electrode potential change of 0.1V one minute after the start of discharge.

[0061] The surface portion of the negative electrode additive layer may have a first layer containing lithium carbonate as a constituent element of the coating. This first layer is primarily formed on the surface of the negative electrode active material. The larger the specific surface area of ​​the negative electrode additive layer, the more easily the negative electrode deteriorates; however, by forming this first layer, negative electrode deterioration can be significantly suppressed. Here, negative electrode deterioration is typically evaluated in the form of the increase in the low-temperature DCR of the electrochemical device during float charging at high temperature using an external DC power supply to apply a certain voltage to the electrochemical device.

[0062] The surface portion of the negative electrode can have a second layer containing a solid electrolyte as a constituent element of the coating. This second layer has a different composition from the first layer and can be distinguished from it. In lithium-ion electrochemical devices, a solid electrolyte interfacial coating (SEI coating) is formed on the negative electrode mix layer during charge and discharge. The second layer can be formed as an SEI coating. The SEI coating plays an important role in the charge-discharge reaction, but if the SEI coating is too thick, the degradation of the negative electrode becomes greater. In contrast, the first layer containing lithium carbonate promotes the formation of a good SEI coating and maintains the SEI coating in a good state during repeated charge-discharge cycles. Therefore, by forming a first layer on the surface portion of the negative electrode mix layer, even when the specific surface area of ​​the negative electrode mix layer is increased to obtain high output, the degradation of the negative electrode can be significantly suppressed.

[0063] In the case where the coating has a first layer and a second layer, at least a portion of the second layer covers at least a portion of the surface of the negative electrode active material through the first layer. That is, at least a portion of the first layer is covered by the second layer. The first layer is located between the surface of the negative electrode active material and the second layer, becoming the base layer of the second layer. By making the first layer the base layer, the second layer is formed into a well-formed SEI coating.

[0064] The second layer may also contain lithium carbonate. When the second layer contains lithium carbonate, the amount of lithium carbonate in the second layer is less than that in the first layer. Using a first layer containing a large amount of lithium carbonate as the substrate layer is a necessary condition for the second layer to form a well-formed SEI film.

[0065] The first layer is formed on the surface of the negative electrode mixture layer before the electrochemical device is assembled. In the electrochemical device assembled using this negative electrode, a second layer (SEI film) of uniform and moderate thickness is formed on the surface of the negative electrode active material through subsequent charge and discharge. The SEI film is formed, for example, by the reaction of the electrolyte with the negative electrode in the electrochemical device. The electrolyte can pass through both the second layer and the first layer, so the entire surface portion including the first and second layers can also be referred to as the SEI film. However, for convenience, in this specification, the second layer is referred to as the SEI film to distinguish it from the first layer.

[0066] The presence of lithium carbonate-containing regions, such as the first layer, can be confirmed, for example, by analysis of the surface portion using X-ray photoelectron spectroscopy (XPS). However, the analytical method is not limited to XPS.

[0067] The thickness of the first layer can be, for example, 1 nm or more. If a longer-term effect is desired, it can be set to 5 nm or more, and if a more reliable effect is desired, it can be set to 10 nm or more. However, if the thickness of the first layer exceeds 50 nm, the first layer itself may become a resistive component. Therefore, the thickness of the first layer can be set to less than 50 nm or less than 30 nm.

[0068] The thickness of the second layer can be, for example, 1 nm or more, or 3 nm or more, as long as it is 5 nm or more. However, if the thickness of the second layer exceeds 20 nm, the second layer itself may become a resistive component. Therefore, the thickness of the second layer can be set to less than 20 nm or less than 10 nm.

[0069] From the viewpoint of reducing the initial low-temperature DCR, the ratio of the thickness A of the first layer to the thickness B of the second layer, A / B, is preferably 1 or less. In this case, the thickness of the second layer is preferably 20 nm or less, and may also be 10 nm or less. However, from the viewpoint of forming a well-formed second layer, A / B is preferably 0.1 or more, for example, the A / B ratio may be 0.2 or more.

[0070] The thicknesses of the first and second layers are determined by analyzing the surface portion of the negative electrode mixture layer at multiple locations (at least five). The average thickness of the first or second layer obtained at these multiple locations is then taken as the thickness of the first or second layer. It should be noted that the negative electrode mixture layer used for the test sample can be peeled off from the negative electrode current collector. In this case, the film formed on the surface of the negative electrode active material near the surface portion constituting the negative electrode mixture layer is analyzed. Specifically, the negative electrode active material covered by the film is collected from the region of the negative electrode mixture layer disposed on the side opposite to the side bonded to the negative electrode current collector and used for analysis.

[0071] XPS analysis of the surface layer of the negative electrode mixture was performed as follows: An argon beam was irradiated onto the coating formed on the surface of the surface layer or the surface of the negative electrode active material within the chamber of an X-ray photoelectron spectrometer. The changes in the spectra attributed to C1s, O1s electrons, etc., with respect to irradiation time were observed and recorded. At this time, from the viewpoint of avoiding analytical errors, the spectra of the outermost surface of the surface layer can be ignored. The thickness of the region where the peak attributed to lithium carbonate was consistently observed corresponds to the thickness of the first layer.

[0072] In the case of a negative electrode removed from an electrochemical device that has undergone specified aging or at least one charge-discharge cycle, the surface portion of the negative electrode mixture layer has an SEI film (i.e., the second layer) containing a solid electrolyte. It has been consistently observed that the thickness of the region attributable to the bond peaks of the compounds contained in the SEI film corresponds to the thickness of the SEI film (i.e., the thickness of the second layer).

[0073] The compounds contained in the SEI coating are selected from those containing elements that can serve as markers for the second layer. Elements that can serve as markers for the second layer can be, for example, elements present in the electrolyte but substantially absent in the first layer (e.g., F). For example, LiF could be selected as a compound containing elements that can serve as markers for the second layer.

[0074] When the second layer contains LiF, if the second layer is measured by X-ray photoelectron spectroscopy, a peak attributable to the LiF bond (F1s) is observed. In this case, the thickness of the region where the peak attributable to the LiF bond is stably observed corresponds to the thickness of the second layer.

[0075] On the other hand, the first layer typically does not contain LiF, and even when the first layer is measured using X-ray photoelectron spectroscopy, the actual F1s peaks attributable to LiF bonds are not observed. Therefore, the thickness of the region where peaks attributable to LiF bonds are not stably observed can be taken as the thickness of the first layer.

[0076] O1s peaks attributable to lithium carbonate can also be observed in the SEI coating. However, the SEI coating formed within the electrochemical device has a different composition than the pre-formed first layer, thus allowing for differentiation. For example, XPS analysis of the SEI coating reveals F1s peaks attributable to LiF bonds, while substantial F1s peaks attributable to LiF bonds are not observed in the first layer. Furthermore, the amount of lithium carbonate in the SEI coating is trace. It should be noted that peaks from compounds such as ROCO₂Li and ROLi can be detected as Li1s peaks.

[0077] When analyzing the first layer with XPS, in addition to the first O1s peak attributed to the C=O bond, a second O1s peak attributed to the Li-O bond can also be observed. The coated region near the surface of the negative electrode active material may contain small amounts of LiOH or Li2O.

[0078] Specifically, when analyzing the first layer of the surface portion constituting the negative electrode mixture layer in the depth direction, a first region and a second region can be observed in order of increasing distance from the outermost surface of the surface portion. The first region observes a first peak (attributed to O1s of C=O bonds) and a second peak (attributed to O1s of Li-O bonds), with the intensity of the first peak being greater than that of the second peak. The second region observes both the first and second peaks, with the intensity of the second peak being greater than that of the first peak. Furthermore, a third region may also exist that is closer to the outermost surface of the surface portion than the first region, observes the first peak, but does not observe the second peak. The third region is easily observed when the thickness of the lithium carbonate-containing region is large.

[0079] It should be noted that the magnitude of the peak intensity can be determined by the height of the peak from the baseline.

[0080] In the center of the thickness direction of the first layer, the C1s peak attributable to the CC bond is usually not substantially observable, or even if it is observed, it is less than half the intensity of the peak attributable to the C=O bond.

[0081] Next, a method for forming a first layer containing lithium carbonate on the surface of the negative electrode mixture layer will be described. The process of forming the first layer can be performed, for example, by vapor phase method, coating method, transfer method, etc.

[0082] As a vapor-phase method, examples include chemical vapor deposition, physical vapor deposition, and sputtering. For instance, lithium carbonate can be deposited onto the surface of the negative electrode mixture layer using a vacuum vapor deposition apparatus. The pressure within the apparatus chamber during vapor deposition is, for example, set to 10... -2 ~10 -5 Pa is sufficient; the temperature of the lithium carbonate evaporation source can be 400–600℃; and the temperature of the negative electrode binder layer can be -20–80℃.

[0083] As a coating method, for example, a microgravure coater is used to coat the surface of the negative electrode with a solution or dispersion containing lithium carbonate and then dried, thereby forming the first layer. The lithium carbonate content in the solution or dispersion is, for example, 0.3 to 2% by mass, and in the case of using a solution, it is a concentration below the solubility (for example, about 0.9 to 1.3% by mass if it is an aqueous solution at room temperature).

[0084] Furthermore, a negative electrode can be obtained by performing a process of forming a second layer containing a solid electrolyte in such a way that it covers at least a portion of the first layer. The surface portion of the obtained negative electrode mixture layer has a first layer and a second layer. The second layer is formed such that at least a portion of it covers at least a portion (preferably the entire surface) of the negative electrode active material, with the first layer in between (i.e., the first layer is used as a base layer).

[0085] The process of forming the second layer is carried out by contacting the negative electrode binder layer with the electrolyte and then allowing it to stand for a specified time. For example, the second layer can be formed on the negative electrode binder layer by performing at least one charge-discharge cycle on the electrochemical device. The process of forming the second layer can also serve as at least part of the lithium-ion pre-doping process of the negative electrode binder layer.

[0086] The process of forming the first layer is preferably performed before the electrode body is formed, but it is not excluded that it may be performed after the electrode body is formed.

[0087] (positive electrode)

[0088] The positive electrode comprises a positive current collector and a positive electrode flux layer supported on the positive current collector. The positive electrode flux layer contains a positive electrode active material reversibly doped with anions, such as carbon materials or conductive polymers. The thickness of the positive electrode flux layer is, for example, 10–300 μm on each single side of the positive current collector.

[0089] The positive current collector uses a sheet-like metal material. This sheet-like metal material can be metal foil, porous metal, etched metal, etc. Suitable metal materials include aluminum, aluminum alloys, nickel, and titanium. Similar to the negative current collector, the positive current collector is preferably a sheet material that does not substantially have through holes.

[0090] The positive current collector is a generally disc-shaped metal plate. Preferably, a through hole is formed in the center of the positive current collector to provide a passage for the non-aqueous electrolyte. The material of the positive current collector is, for example, aluminum, aluminum alloy, titanium, stainless steel, etc. The material of the positive current collector can be the same as that of the positive current collector.

[0091] As the carbon material used as the positive electrode active material, porous carbon materials are preferred, such as activated carbon, and carbon materials exemplified as negative electrode active materials (e.g., non-graphitized carbon). Examples of raw materials for activated carbon include wood, coconut shells, coal, asphalt, and phenolic resins. Activated carbon that has undergone activation treatment is preferred.

[0092] The average particle size of activated carbon is not particularly limited, but it is preferably less than 20 μm, and more preferably 3 μm to 15 μm.

[0093] The specific surface area of ​​the positive electrode flux layer roughly reflects the specific surface area of ​​the positive electrode active material. For example, the specific surface area of ​​the positive electrode flux layer might be 600 m². 2 / g or more and 4000m 2 / g or less is acceptable, preferably 800m 2 / g or more and 3000m 2 / g or less. The specific surface area of ​​the positive electrode mixture layer is the BET specific surface area determined using a measuring apparatus based on JIS Z8830 (e.g., Shimadzu Corporation TriStarII3020). Specifically, the electrochemical device is disassembled, and the positive electrode is removed. Next, the positive electrode is cleaned with DMC and dried. Then, the positive electrode mixture layer is peeled off from the positive electrode current collector, and a sample of approximately 0.5g of the positive electrode mixture layer is collected. Next, the specific surface area of ​​the collected sample is determined according to the method for determining the specific surface area of ​​the negative electrode mixture layer described above.

[0094] Activated carbon preferably comprises 50% or more by mass of the positive electrode active material, more preferably 80% or more by mass, and even more preferably 95% or more by mass. Furthermore, activated carbon preferably comprises 40% or more by mass of the positive electrode additive layer, more preferably 70% or more by mass, and even more preferably 90% or more by mass.

[0095] The positive electrode binder layer contains a positive electrode active material as a necessary component, and optional components include conductive additives, binders, etc. Examples of conductive additives include carbon black and carbon fiber. Examples of binders include fluoropolymers, acrylic resins, rubber materials, and cellulose derivatives.

[0096] The positive electrode additive layer is formed, for example, by mixing positive electrode active material, conductive agent and binder with a dispersion medium to prepare a positive electrode additive slurry, and then coating the positive electrode additive slurry onto the positive electrode current collector and drying it.

[0097] As the conductive polymer used as the positive electrode active material, π-conjugated polymers are preferred. Examples of π-conjugated polymers include polypyrrole, polythiophene, polyfuran, polyaniline, polythiophene vinylidene, polypyridine, or their derivatives. They can be used alone or in combination of two or more. The weight-average molecular weight of the conductive polymer is, for example, 1000 to 100000. It should be noted that derivatives of π-conjugated polymers refer to polymers with π-conjugated polymers such as polypyrrole, polythiophene, polyfuran, polyaniline, polythiophene vinylidene, and polypyridine as their basic backbone. For example, polythiophene derivatives include poly(3,4-ethylenedioxythiophene) (PEDOT).

[0098] Conductive polymers can be formed, for example, by immersing a carbon-layered positive electrode current collector in a reaction solution containing a monomer of the conductive polymer, and then electrolytically polymerizing the monomer in the presence of the positive electrode current collector. In electrolytic polymerization, the positive electrode current collector and the counter electrode are immersed in the reaction solution containing the monomer, with the positive electrode current collector acting as the anode, and current flows between them. Conductive polymers can also be formed by methods other than electrolytic polymerization. For example, conductive polymers can be formed by the chemical polymerization of the monomer. In chemical polymerization, the monomer is polymerized using an oxidizing agent or the like in the presence of a positive electrode current collector.

[0099] The monomers used in electrolytic polymerization or chemical polymerization can be polymeric compounds capable of forming conductive polymers through polymerization. These monomers may include oligomers. Examples of monomers used include aniline, pyrrole, thiophene, furan, thiophene acetylene, pyridine, or their derivatives. They can be used alone or in combination of two or more. Aniline, in particular, readily grows on the surface of a carbon layer through electrolytic polymerization.

[0100] Electrolytic polymerization or chemical polymerization can be carried out using reaction solutions containing anions (dopants). Excellent conductivity is achieved by doping π-electron conjugated polymers with dopants. Examples of dopants include sulfate ions, nitrate ions, phosphate ions, borate ions, benzenesulfonate ions, naphthalenesulfonate ions, toluenesulfonate ions, methanesulfonate ions, perchlorate ions, tetrafluoroborate ions, hexafluorophosphate ions, and fluorosulfate ions. Dopants can also be polymeric ions. Examples of polymeric ions include ions of polyvinylsulfonic acid, polystyrene sulfonic acid, polyallyl sulfonic acid, polypropylene sulfonic acid, polymethylpropylene sulfonic acid, poly(2-acrylamido-2-methylpropanesulfonic acid), polyisoprene sulfonic acid, and polyacrylic acid.

[0101] (spacer)

[0102] As spacers, nonwoven fabrics made of cellulose fibers, nonwoven fabrics made of glass fibers, microporous membranes made of polyolefins, woven fabrics, or nonwoven fabrics can be used. The thickness of the spacer is, for example, 8 to 300 μm, preferably 8 to 40 μm.

[0103] (electrolytes)

[0104] Electrolytes exhibit lithium-ion conductivity and, for example, contain lithium salts and solvents that dissolve the lithium salts. The lithium salt anions reversibly and repeatedly dope and dedope the positive electrode. Lithium ions from the lithium salt are reversibly absorbed and released by the negative electrode.

[0105] Examples of lithium salts include LiClO4, LiBF4, LiPF6, LiAlCl4, LiSbF6, LiSCN, LiCF3SO3, LiFSO3, LiCF3CO2, LiAsF6, and LiB. 10 Cl 10 Examples of lithium salts include LiCl, LiBr, LiI, LiBCl4, LiN(FSO2)2, and LiN(CF3SO2)2. These can be used individually or in combination of two or more. Salts containing fluoride anions are preferred, and lithium bis(fluorosulfonyl)imide, i.e., LiN(SO2F)2, is particularly preferred. The concentration of the lithium salt in the electrolyte at the state of charge (SOC) of 90–100% is, for example, 0.2–5 mol / L. Hereinafter, LiN(SO2F)2 will be referred to as LiFSI. For example, 80% by mass or more of the lithium salt can be LiFSI.

[0106] By using LiFSI, the increase rate of low-temperature DCR tends to decrease significantly. It is believed that LiFSI has the effect of reducing the degradation of both positive and negative electrode active materials. It is thought that in salts containing fluoride anions, the stability of FSI anions is excellent, thus reducing the likelihood of byproduct formation and preventing damage to the surface of active materials, which facilitates smooth charge and discharge. Especially when increasing the capacity of the positive electrode and the specific surface area of ​​the negative electrode binder layer, the degradation inhibition effect (the effect of suppressing the increase of low-temperature DCR) brought about by the use of LiFSI, which significantly reduces the impact of byproducts on each active material, becomes significant.

[0107] As solvents, cyclic carbonates such as ethylene carbonate, propylene carbonate, and butyl carbonate; chain carbonates such as dimethyl carbonate, diethyl carbonate, and methyl ethyl carbonate; aliphatic carboxylic acid esters such as methyl formate, methyl acetate, methyl propionate, and ethyl propionate; lactones such as γ-butyrolactone and γ-valerolactone; and 1,2-dimethoxyethane (DME), 1,2-diethoxyethane (DEE), and ethoxymethoxyethane can be used. Chain ethers such as (EME), cyclic ethers such as tetrahydrofuran and 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, acetamide, dimethylformamide, dioxolane, acetonitrile, propionitrile, nitromethane, ethylene glycol diethyl ether, trimethoxymethane, sulfolane, methylsulfolane, 1,3-propanesulfonic acid lactone, etc. These can be used alone or in combination of two or more.

[0108] Various additives can be included in the electrolyte as needed. For example, as an additive to form a lithium-ion conductive film on the negative electrode surface, unsaturated carbonates such as vinylene carbonate, vinyl ethylene carbonate, and divinyl ethylene carbonate can be added.

[0109] [Example]

[0110] The present invention will now be described in more detail based on embodiments, but the present invention is not limited to the embodiments. It should be noted that a summary of the structure of the various devices fabricated below is shown in Table 1.

[0111] (Device A1)

[0112] (1) Production of the positive electrode

[0113] Prepare an aluminum foil (positive electrode current collector) with a thickness of 30 μm. Meanwhile, disperse 88 parts by mass of activated carbon (average particle size 5.5 μm) as the positive electrode active material, 6 parts by mass of polytetrafluoroethylene as a binder, and 6 parts by mass of acetylene black as a conductive agent in water to prepare a positive electrode slurry. Coat both sides of the aluminum foil with the obtained positive electrode slurry, dry the coating, and calender it to form a positive electrode slurry layer, thus obtaining the positive electrode. Form a 10 mm wide exposed portion of the positive electrode current collector at its length end.

[0114] (2) Fabrication of the negative electrode

[0115] Prepare a copper foil (negative electrode current collector) with a thickness of 8 μm. The copper foil prepared is without through holes. Meanwhile, prepare a negative electrode slurry by dispersing 94 parts by mass of non-graphitized carbon (average particle size 5 μm), 1 part by mass of carboxycellulose, and 5 parts by mass of carbon black in water. The carbon black used has a BET specific surface area of ​​800 m². 2 / g of carbon black. The obtained negative electrode slurry is coated on both sides of a copper foil, the coating is dried, and then calendered to form a negative electrode slurry layer, thus obtaining the negative electrode. The thickness of the negative electrode slurry layer is 32μm on one side.

[0116] For the obtained negative electrode, the BET surface area of ​​the negative electrode mixture layer was measured using the method described above, and the result was 40 m². 2 / g.

[0117] Then, the negative electrode was placed in an electrolytic cell filled with an electrolyte that is conductive to lithium ions. Similarly, an SUS metal plate carrying metallic lithium as the working electrode was placed in the electrolytic cell, and a voltage was applied between the negative electrode and the working electrode with a spacer between them. The working electrode was used as the positive electrode and charged at a constant current (CC) of 0.1 mA until the battery voltage reached 0.01 V. Then, it was charged at a constant voltage (CV) for 5 hours for pre-doping. As the electrolyte solvent, a solvent containing 1% by mass of vinylene carbonate (VC) was used, which was prepared by mixing ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) in a volume ratio of 1:2:7. LiPF6 as a lithium salt was added to the mixed solvent at a concentration of 1.2 mol / L to prepare the electrolyte. After pre-doping, the negative electrode was cleaned with dimethyl carbonate (DEC) to obtain a negative electrode pre-doped with lithium ions.

[0118] (3) Fabrication of the electrode body

[0119] The positive and negative electrodes are separated by a cellulose nonwoven fabric spacer (25 μm thick) and wound into a cylindrical shape to form the electrode body. The positive current collector protrudes from one end face of the wound body, and the negative current collector protrudes from the other end face. Disc-shaped positive and negative current collector plates are then welded to the exposed positive and negative current collector portions, respectively.

[0120] (4) Preparation of non-aqueous electrolyte

[0121] A solvent was prepared by adding 0.2% by mass of vinylene carbonate to a mixture of propylene carbonate and dimethyl carbonate in a volume ratio of 1:1. A non-aqueous electrolyte was prepared by dissolving LiFSI as a lithium salt in the resulting solvent at a concentration of 1.2 mol / L.

[0122] (5) Assembly of electrochemical devices

[0123] The electrodes are housed within a bottomed battery casing with an opening. A connector lead, which connects to the positive current collector, is attached to the inner surface of a sealing plate. Additionally, the negative current collector is soldered to the inner bottom surface of the battery casing. After adding a non-aqueous electrolyte into the battery casing, the opening is sealed with the sealing plate, and the battery is assembled. Figure 1 An electrochemical device as shown.

[0124] Then, while applying a charging voltage of 3.8V between the terminals of the positive and negative electrodes, aging was carried out at 60°C to complete the pre-doping of lithium ions into the negative electrode.

[0125] (6) Evaluation

[0126] [Evaluation 1: Determination of the capacity (energy density) of electrochemical devices]

[0127] Perform the initial charge and discharge under the following conditions.

[0128] For electrochemical devices that have just aged, at an environment of 25°C, with a positive electrode area of ​​2 mA / cm², 2 Constant current charging was applied until the voltage reached 3.8V, and then the 3.8V voltage was maintained for 10 minutes. Then, at 25°C, the voltage was increased by 2mA / cm² per unit positive electrode area. 2 A constant current discharge was performed until the voltage reached 2.2V. During the discharge, the time t (sec) required for the voltage to drop from 3.3V to 3.0V was measured. Using the measured time t, the initial capacity C1 of the electrochemical device was calculated using the following equation (A).

[0129] Capacity C1 = Id × t / V (A)

[0130] It should be noted that in equation (A), Id is the current value during discharge (current density per unit positive electrode area, 2 mA / cm²). 2 × Positive electrode area), V is the value obtained by subtracting 3.0V from 3.3V (0.3V).

[0131] Based on the capacity C1, the energy density E (Wh / L) of the electrochemical device is evaluated using the following equation (B). In equation (B), V1 is the upper limit voltage during charging and discharging (3.8V), and V2 is the lower limit voltage (2.2V). CELL This refers to the volume occupied by the device.

[0132] E=(1 / 2)×C1×(V1 2 -V2 2 ) / (3600×V CELL (B)

[0133] [Evaluation 2: Determination of power density of electrochemical devices]

[0134] Next, using the discharge curve obtained above (vertical axis: discharge voltage, horizontal axis: discharge time), an approximate straight line is calculated for the period from 0.5 seconds to 2 seconds after the start of discharge. The intercept voltage of this approximate straight line (voltage at 0 seconds after the start of discharge) VS is then calculated. The value (V0-VS) obtained by subtracting the voltage VS from the voltage V0 at the start of discharge (0 seconds after the start of discharge) is taken as the voltage drop ΔV at the start of discharge. ΔV and the discharge current value (current density per unit positive electrode area, 2 mA / cm²) are then used. 2 × positive electrode area), calculate the internal resistance (DCR) R1 (Ω) of the electrochemical device according to the following formula (C).

[0135] Internal resistance R1 = ΔY / Id (C)

[0136] Based on R1, the power density P (kW / L) of the electrochemical device is evaluated by the following equation (D).

[0137] P=(V1-V2)×V2 / (1000×R1×V CELL (D)

[0138] [Evaluation 3: Determination of Cyclic Characteristics of Electrochemical Devices]

[0139] Repeat the charge-1 and discharge-1 cycles described below 100,000 times. Based on the time change of voltage during the 100,000th discharge-1 cycle, similar to the derivation of the initial capacity C1, calculate the capacity C of the electrochemical device after the cycle test based on the above equation (A). 100000 .

[0140] (Charging-1) For electrochemical devices, at 25°C, with an energy density of 2 mA / cm² per unit positive electrode area... 2 The current density is constant-current charged until the voltage reaches 3.8V. Then, the applied voltage of 3.8V is maintained for 10 minutes.

[0141] (Discharge-1) Then, at 25°C, with an energy density of 2 mA / cm² per unit positive electrode area. 2 The current density is constant current discharge until the voltage reaches 2.2V.

[0142] Find the capacity C 100000 The change in capacity C1 relative to the initial capacity ΔC is used to evaluate the cycling characteristics using the following equation (E). The evaluation results are shown in Table 1.

[0143] ΔC=((C 100000 / C1)-1)×100 (E)

[0144] (Components A2-A7, B1, B2)

[0145] The thickness of the copper foil (used as the negative electrode current collector), the content of the conductive additive (carbon black) in the negative electrode slurry, the specific surface area of ​​the negative electrode slurry layer, and the thickness of one side were varied as shown in Table 1. It should be noted that while varying the content of the conductive additive in the negative electrode slurry, the content of carboxycellulose (used as a binder) was kept constant, and the content of non-graphitized carbon (used as the negative electrode active material) decreased (increased) as the content of the conductive additive increased (decreased).

[0146] In addition, devices A2 to A7, B1, and B2 were assembled and evaluated in the same manner as device A1. The results are shown in Table 1.

[0147] (Components B3, B4)

[0148] As the negative current collector, an open copper foil with an opening of 0.075 mm in diameter (opening ratio 23%) is prepared.

[0149] In the fabrication of the electrode body, the positive electrode and the undoped negative electrode are wound into a column shape with a spacer made of cellulose nonwoven fabric (25μm thick) in between to form the electrode body.

[0150] In a bottomed battery casing with an opening, the electrode body and lithium sheet are housed together. The connector lead, which connects to the positive current collector, is connected to the inner surface of a sealing plate. Additionally, the negative current collector is soldered to the inner bottom surface of the battery casing. After adding a non-aqueous electrolyte into the battery casing, the opening is sealed with the sealing plate, and the battery is assembled. Figure 1An electrochemical device as shown. The amount of pre-doped lithium is set such that the negative electrode potential in the non-aqueous electrolyte after pre-doping is below 0.2V relative to metallic lithium.

[0151] In addition, devices B3 and B4 were assembled and evaluated in the same manner as device A1. Specifically, the thickness of the negative current collector in device B3 was set to 8 μm, and the thickness of the negative current collector in device B4 was set to 20 μm. The evaluation results are shown in Table 1.

[0152] For devices A1–A7 and B1–B4, after the initial charge-discharge cycle, the devices were disassembled and the negative electrode was removed. A half-cell was constructed using a reference electrode (lithium foil) and the negative electrode, and the half-cell was brought into contact with a non-aqueous electrolyte. The potential of the negative electrode relative to a reference voltage was measured. The results showed that the potential of the negative electrode for devices A1–A7 and B1–B4 was below 0.2V.

[0153] [Table 1]

[0154]

[0155] Based on the comparison of devices A1-A7, B1, and B2, when using a negative electrode current collector without through holes, the specific surface area of ​​the negative electrode flux layer is set to 30m². 2 / g or more and 60m 2 Among devices A1 to A7 with a capacity of less than / g, high energy density and high power density can be maintained. In addition, the cycle characteristics are also high.

[0156] In devices B3 and B4, the strength of the negative current collector is low due to the use of perforated foil as the negative current collector. For device B3, where the thickness of the negative current collector is set to 8 μm, the negative electrode breaks during the fabrication of the wound body, making it impossible to obtain an electrode body. In device B4, where the thickness of the negative current collector is set to 20 μm, although an electrode body can be fabricated, both energy density and power density are reduced.

[0157] In addition, graphite is used instead of hard carbon (difficult-to-graphitize carbon) in the negative electrode active material, and the electrochemical device is fabricated in the same manner as device A1. In this case, the expansion and contraction during charge-discharge cycles are greater than with hard carbon, resulting in reduced reliability.

[0158] Industrial availability

[0159] The electrochemical device of the present invention is suitable, for example, for use in vehicles.

[0160] Explanation of reference numerals in the attached figures

[0161] 100: Electrode body

[0162] 10: Positive electrode

[0163] 11x: Exposed portion of the positive current collector

[0164] 13: Positive current collector

[0165] 15: Connector lead wire

[0166] 20: Negative electrode

[0167] 21x: Exposed portion of the negative current collector

[0168] 23: Negative current collector

[0169] 30: Spacer

[0170] 200: Electrochemical Devices

[0171] 210: Battery casing

[0172] 220: Sealing board

[0173] 221: Washer.

Claims

1. An electrochemical device comprising: An electrode body comprising a positive electrode, a negative electrode, and a spacer between the positive electrode and the negative electrode; and Electrolytes, which contain lithium salts The negative electrode comprises a negative electrode current collector and a negative electrode additive layer supported on the negative electrode current collector. The negative electrode mixture layer contains non-graphitized carbon as a negative electrode active material that is reversibly doped with lithium ions. The negative current collector does not have a through hole. The specific surface area of ​​the negative electrode mixture layer is 30m². 2 / g or more and 60m 2 / g or less In the discharge state, the potential of the negative electrode is less than 0.2V relative to the Li counter electrode. The surface portion of the negative electrode mixture layer has a first layer containing lithium carbonate and a second layer containing a solid electrolyte as a reaction product of the electrolyte, with at least a portion of the first layer being covered by the second layer.

2. The electrochemical device according to claim 1, wherein, The second layer contains lithium carbonate. The second layer contains less lithium carbonate than the first layer.

3. The electrochemical device according to claim 1 or 2, wherein, The thickness of the first layer is greater than 1 nm and less than 50 nm. The thickness of the second layer is greater than 1 nm and less than 20 nm.

4. The electrochemical device according to claim 1 or 2, wherein, The ratio A / B of the thickness A of the first layer to the thickness B of the second layer is greater than 0.1 and less than 1.

5. The electrochemical device according to claim 1 or 2, wherein, When the surface layer is analyzed in the depth direction using X-ray photoelectron spectroscopy, the first layer has: a first region in the O1s spectrum where the peak intensity of the first peak belonging to the C=O bond is greater than the peak intensity of the second peak belonging to the Li-O bond, and a second region where the peak intensity of the first peak is less than the peak intensity of the second peak. The second region is located at a deeper level than the first region.

6. The electrochemical device according to claim 5, wherein, A third region has the first peak observed but the second peak not observed, located closer to the outermost surface of the surface layer than the first region.

7. The electrochemical device according to claim 1 or 2, wherein, The negative electrode mixture layer contains conductive additives. The conductive additive accounts for more than 3% by mass and less than 15% by mass in the negative electrode compound layer.

8. The electrochemical device according to claim 1 or 2, wherein, The negative electrode mixture layer contains conductive additives. The specific surface area of ​​the conductive additive is 800 m². 2 / g or more.

9. The electrochemical device according to claim 8, wherein, The conductive additive includes carbon black.

10. The electrochemical device according to claim 1 or 2, wherein, The thickness of the negative electrode current collector is less than 15 μm. The thickness of the negative electrode compound layer is 25 μm or more.

11. The electrochemical device according to claim 1 or 2, wherein, The electrode body is a cylindrical wound body formed by winding the strip-shaped positive electrode and the strip-shaped negative electrode with the spacer in between.

Citation Information

Patent Citations

  • Negative electrode coating film and coating composition for forming electrode coating film of lithium ion capacitor

    JP2010098020A

  • Nonaqueous lithium power storage element

    JP2018056409A

  • Nonaqueous lithium power storage element

    JP2018056432A